GST: Awareness Steps Taken by the Government at State and Centre and the Opinion among People in Tamilnadu - KRISHNAN, N. AMUTHA; USHA, S. (International Journal of Psychosocial Rehabilitation, 2020)
India Introduced GST in July 1, 2017. In a democratic country like India, a high degree of knowledge about GST is needed among people to get their cooperation to effectively implement GST and make it successful. This project seeks to find out the steps taken by both central and state Governments to create GST awareness and the effectiveness of those steps by getting the opinion about GST from few samples. The project outcomes that the steps taken are effective in reaching business people than that of common man. Based on the findings, certain suggestions are made which might increase the effectiveness of the measures taken by the Government.